Effects of residual particles and multiply charged particles of a polystyrene latex particle on the particle filtration efficiency of a medical face masks - Sardyoung, Papol; Intra, Panich; Lawong, Theerachot; Rattanachan, Wisanapat (Engineering and Technology Horizons, 2025)
The objective of this study is to elucidate the impact of residual particles and multiply charged particles of polystyrene latex (PSL) particles on the particle filtration efficiency of a medical face mask. Adhering to the ASTM F2299 test methodology, this investigation employed a PSL particle (Thermo ScientificTM Dri-CalTM) with a diameter of 100 nanometers and a geometric standard deviation of approximately 1.6%. The scanning mobility particle sizer (SMPS) was utilized to ascertain the size distribution of PSL particles both upstream and downstream of the test face mask, thereby determining the particle filtration efficiency of the face mask for residual particles and multiply charged particles at various PSL particle-to-DI water ratios. The PSL particle-to-DI water ratios employed in this study were 10, 20, and 100 drops per 200 mL, respectively. The findings revealed that PSL suspension residual particles with a mobility diameter less than 60 nanometers, as well as multiple charged particles with a mobility diameter exceeding 100 nanometers, introduced complexity to purportedly monodisperse particle aerosols. An increase in PSL suspension concentration resulted in a heightened relevance of the residual peak. At elevated concentrations, PSL multiply charged particles became discernible in the size distribution. Furthermore, it was demonstrated that as the PSL particle-to-DI water ratios increased, the particle filtration efficiency of the test face mask diminished for both single charged particles and multiply charged particles (+2, +3, +4, and +5).